1992
DOI: 10.1177/002383099200500108
|View full text |Cite
|
Sign up to set email alerts
|

Incontinence and Troublesome Behaviors Predict Institutionalization in Dementia

Abstract: Factors predicting the early institutionalization of demented patients were studied in 143 outpatients using univariate and multivariate life-table methods. Four types of factors were evaluated for prognostic value: severity of functional impairment, behavioral disorders, individual patient characteristics, and type of caregiver. After follow-up of 19 +/- 12 months, 51 patients had been institutionalized. Increased global severity of dementia, the presence of troublesome and disruptive behaviors, and incontine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
128
0
4

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(136 citation statements)
references
References 22 publications
4
128
0
4
Order By: Relevance
“…35,53 Ween et al 35 reported that 46% of 145 stroke survivors with incontinence returned to their own home after hospitalization compared with 79% of 278 continent stroke survivors. Only 15% of those initially continent after their stroke were later admitted to a nursing home compared with 38% of the incontinent group.…”
Section: Progress Of the Stroke Survivor With Incontinencementioning
confidence: 99%
“…35,53 Ween et al 35 reported that 46% of 145 stroke survivors with incontinence returned to their own home after hospitalization compared with 79% of 278 continent stroke survivors. Only 15% of those initially continent after their stroke were later admitted to a nursing home compared with 38% of the incontinent group.…”
Section: Progress Of the Stroke Survivor With Incontinencementioning
confidence: 99%
“…[1][2][3] They are associated with increased caregiver burden, 4 institutionalisation, 5 progression 6 and care costs. 1 Many people with Alzheimer's disease are treated with antipsychotics, often to ameliorate neuropsychiatric symptoms.…”
mentioning
confidence: 99%
“…Approximately 1.6 million (5%) of those older adults live in long-term care facilities (Aiken, 2001). Problem behaviors are the most common precipitating factor for institutionalization (O'Donnell et al, 1992;Plaud, Moberg, & Ferraro, 1998), and up to 80% of nursing home residents exhibit problem behaviors such as physical aggression, wandering, and repetitive vocalizations (Allen-Burge, Stevens, & Burgio, 1999;Meeks, 1996).…”
mentioning
confidence: 99%